The study of Ancient slavery and the path to renewal: a critique - Ulrike Roth (Esboços)
This response highlights an underlying issue of the contribution offered by Joly and Knust – namely the problematic relationship between the top-down proposal of a theoretical framework for the study of ancient slavery on the one hand, and on the other hand the role of practices of domination, however light-touch, in the structuring of social relations in academia, and by extension contemporary society at large. In so doing, the response articulates a broader critique of top-down research agendas, challenging also the establishment, a priori, of theoretical frameworks for research in – that is, for – the field as a whole.